Juego y su incidencia en el desarrollo psicomotriz de los estudiantes de primer año de la escuela de educación básica “Eugenio Espejo” del cantón Baba periodo lectivo 2017 - Cajas Bonilla, Silvana Yadira (2017)
Our investigative work is solely based on the aulic problems, which we detect in pre-professional practices, related to the form in which the development of the psychometricity of children of this educational unit is given, which is strengthened by conventional teaching resources, do not consider the game as a pedagogical tool, but alone as an occasional distractive activity. Neither siquuierahas been taken into account the natural environment where children live, which have a diversity of playual elements, as the traditional channels and games, with which they develop in practical life all their capacities. We have justified this investigation, arguing their importance and impact, both for the own institution, as well as for others that are facing a similar situation. On the other hand, we have founded our work from science, which appears consigned in the conceptual framework and in the theoretical posture, on the other hand, all the information documented here, has been contrasted with the result casted by the surveys, and which it assumes the mode of interpretation, conclusions and recommendations. Finally describe the proposal, centralized in the methodology of the game, with which it is intended to revert the current way of potentiating psychomotricity to our children, so that we ensure that these, are developed integrally, which therefore understand, all the aspects of his life: socio-cultural, affective, cognitive, and by certain physical.